Resonance matching for piezoelectric vibration energy harvesters under impulse excitation - Kota MORISHITA; Yuya TANAKA; Gen HASHIGUCHI; Hiroshi TOSHIYOSHI; Takaaki SUZUKI (Mechanical Engineering Journal)
A vibration energy harvester generates power by utilizing resonance. Stationary sine-wave excitation is a common method of evaluating vibration energy harvesters. However, environmental vibrations are often non-stationary. For example, human vibrations are often impulse vibrations with large instantaneous accelerations. In this study, we applied impulse vibrations to a piezoelectric vibration energy harvester (PVEH) and evaluated the input acceleration of the impulse vibrations, deflection, and output power waveforms. The PVEH was fabricated into a cantilever shape, and the resonance frequencies were varied by attaching different proof masses. Based on the results of the experiment and FEM analysis, it was observed that the pulse width of the input impulse vibration and the resonance frequency of the PVEH at which the maximum output power was obtained were inversely proportional. The conventional design method of matching the resonance frequency of a PVEH to the number of impulse vibrations per second results in challenges regarding the size and complexity of the device. However, the proposed method focuses on the acceleration waveform of impulse vibrations, making it effective even when the input vibrations are non-periodic. In addition, the proposed design method can generate high power with a small and simple structure. Therefore, it is promising for application in wearable devices.